PATRONES DE COMPETENCIA INTRAESPECIFICA EN HORMIGAS ECTATOMMA RUIDUM (FORMICIDAE:PONERINAE) - Amat García, Germán; Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
The interactions between 2 colonies of Ponerinae ants, Ectatomma ruidum, established in the dry caducifolium forest of Paloverde, Costa Rica, were studied. Three types of antagonisms were identified: contact, aggresion and theft. The pattems of daily foraging show a high similarity between colonies, a fact that increases the probability for antagonism to occur. The size of the colonies, the erra tic paths of the 1ndividuals while foraging and the absence of boundary limiting pheromones seem to be the responsiblefactors for the interespecific competing pattems identified in Ectatomma ruidum.